AFRICAN SWINE FEVER IN RUSSIAN FEDERATION: ECONOMIC IMPACT - V. M. Gulyonkin; I. M. Klinovitskaya; O. N. Petrova; A. K. Karaulov; D. A. Lozovoy (Ветеринария сегодня, 2018)
Following the results of the earlier studies the economic losses due to African swine fever amounted to about 26.56 bln RUB (5.4% inflation-adjusted). In 2016 ASF further spread in the population of domestic pigs and wild boars in the 27 Subjects of the Russian Federation. All disease outbreaks were reported in the European part of the Russian Federation. Total of 26 infected regions were reported where ASF was diagnosed in domestic pigs and 15 infected regions were reported where ASF was detected in wild boars. In the Ivanovo Oblast the ASF was diagnosed only in wild boars (one case). In 15 RF Subjects the disease was reported both in domestic pigs and wild boars. Estimated data demonstrated that economic losses due to ASF outbreaks in domestic pigs and wild boars will amount to 7.89 bln RUB this year. Total economic losses due to ASF spread in the country in 2008-2016 will amount to about 34.45 bln RUB in monetary terms.